The Effect of Trust, Easy and Company Image on The Decision to Use Livin By Mandiri (Jakarta Kota Branch) - Muhammad Ananda Putra Kushendar; Elwisam Elwisam; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to analyze the effect of trust, convenience and company image on the decision to use Livin By Mandiri. Data collection techniques in this study were obtained from the results of distributing questionnaires to 100 respondents who were customers of Bank Mandiri and at the same time users of the Livin By Mandiri application with certain criteria. The sampling technique used in this study is probability. Analysis of the data used in this study using multiple linear regression analysis which obtained the results of the regression. The results shown in this study that Trust, Ease and company image have a positive effect on the decision to use Livin By Mandiri. In improving the decision to use the Livin By Mandiri application, Bank Mandiri has made significant changes to the Livin By Mandiri application, which is expected that the users or customers of Bank Mandiri can make transactions faster and easier.